Delay in seeking treatment and associated factors among pulmonary tuberculosis patients attending public health facilities in the Metekel zone, Benishangul Gumuz region, Western Ethiopia - Animut, Yaregal; Godno, Abera Birhanu; Nigatu, Solomon Gedlu; Abiy, Saron Abeje (Frontiers in Public Health, 2024)
Background Tuberculosis is a major global public health problem and a leading cause of morbidity and mortality in Ethiopia. TB prevention and control in low-income countries, such as Ethiopia, face significant challenges, including late detection and treatment initiation. A delay in the initiation of tuberculosis treatment increases the morbidity and mortality of patients and community transmission. Therefore, this study aimed to assess patient delay and associated factors among pulmonary tuberculosis patients attending public health facilities in the Metekel Zone, Benishangul Gumuz Region, Western Ethiopia. Methods An institution-based cross-sectional study was conducted from March to August 2020 among newly diagnosed pulmonary tuberculosis patients. All pulmonary tuberculosis patients (416) who came to all public health facilities of the Metekel zone for treatment during the period were included. Data were collected through face-to-face interviews using a structured and pretested questionnaire. A multivariable logistic regression was fitted to identify independent factors for delay in seeking treatment among PTB patients. Adjusted odds ratios with 95% CIs were determined, and variables with p values <0.05 were considered statistically significant. Results Nearly three-fourths 302 (72.6, 95% CI: 68.5, 76.7) of the patients were delayed in seeking medical advice, with a median patient delay of 27 days (IQR: 21–31). Age of the patients [above 54 years (AOR = 2.65, 95% CI: 1.30, 5.40), 36–54 years (AOR = 1.86, 95% CI: 1.14,3.02)], family size of 5 members and above (AOR = 1.62, 95% CI: 1.10–3.14), travel time above 60 min (AOR = 3.65, 95% CI: 1.55, 8.60), history of visits to informal care providers (AOR = 1.74, 95% CI: 1.11, 3.14), and poor knowledge about PTB (AOR = 1.64, 95% CI: 1.04–2.44) were statistically significant factors associated with delays in seeking treatment among PTB patients. Conclusion Most pulmonary tuberculosis patients delay seeking medical advice for their illnesses. Delays in seeking treatment were associated with older age, large household size, longer travel time to reach the nearby health facility, visiting informal care providers, and poor knowledge about pulmonary tuberculosis. Hence, it is crucial to consider community screening programs, enhance public awareness, and ensure the accessibility of TB diagnostic and treatment services.